FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECACATAN PADA PENDERITA KUSTA BARU DI RUMAH SAKIT KUSTA KEDIRI - Wahjudi, Pudjo; Khoiriah, Ulfa Azimatul (IKESMA, 2010)
Leprosy still becomes a public health problem in Indonesia. Many affected leprosy come to the hospital when they are having a disability. Number of disabled leprosy patients for the last 3 years (2006-2008) in Kediri Leprosy Hospital are 263 (79, 22%) from 332 new leprosy patients. Leprosy is high potential to create disability, but it can be prevented by an early medical examination and a regular medical treatment. Leprosy is still becoming a big medical problem and also raising social, economic, and cultural problems. This research is aiming to analyzing influential factors towards disability levels of newly leprosy patients at the Kediri Leprosy Hospital, namely; age, sex, education, occupation, and medical record. The final result is expected to be guidance for hospital in increasing a quality of services towards leprosy patients.Â  This research is an analytical research. Based on the time, this research is included into retrospective research with cross sectional approach. The populations in this research are 116 newly leprosy patients with sampling 53 patients. The sample is collected with simple random sampling technique. Type of collected data is secondary data from medical record of the patients and the data are analyzed with logistic regression examination. The research shows that Age factor is constant with p=1.00 (p>0.05), Sex and Education factor do not influent to disability levels significantly with each: p=0.438 (p>0.05) and p=0.143(p>0.05). Finally, Occupation and Medical Record are significantly influencing to disability level with value each: p=0.004 (p<0.05) and p=0.004 (p<0.05). Recommendation of this research is expecting to health worker using active method to find leprosy patients through intensive contact survey program in patient families and their community to prevent number of people affected by leprosy. Key words: leprosy, new affected leprosy, disability on leprosy